Complete genome sequence of the largest known flavi-like virus, Diaphorina citri flavi-like virus, a novel virus of the Asian citrus psyllid, Diaphorina citri - Matsumura, Emilyn E. [UNESP]; Nerva, Luca; Nigg, Jared C.; Falk, Bryce W.; Nouri, Shahideh (American Society for Microbiology, 2016)
A novel flavi-like virus tentatively named Diaphorina citri flavi-like virus (DcFLV) was identified in field populations of Diaphorina citri through small RNA and transcriptome sequencing followed by reverse transcription (RT)-PCR. We report here the complete nucleotide sequence and genome organization of DcFLV, the largest flavi-like virus identified to date.